ANALISIS SEMIOTIK CHARLES SANDERS PIERSE DALAM MEMAKNAI PESAN DAKWAH PADA AKUN TIKTOK @aabelkarimy - Askolani, Muhammad; Ulfain, Ulfain; Mustika, Ika (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2023)
Abstract : In the context of the @aabelkarimy TikTok account, semiotic analysis can help identify and analyze religious symbols, religious signs, or cultural references used in da'wah videos to strengthen messages and influence audiences. TikTok is a social media platform focused on short video content. In this context, visual communication is very important to convey da'wah messages. Semiotic analysis helps to understand the visual signs used in videos, such as body movements, facial expressions, or visual symbols, to describe and interpret da'wah messages. Da’wah messages often have deeper and more complex meanings, especially when conveyed through social media such as TikTok. Semiotic analysis helps to analyze the signs used in da'wah videos and relate them to the context of culture, religion or related values to understand the meaning of the message to be conveyed. This study aims to describe da'wah messages in the form of aqidah, sharia and moral messages. This research is a qualitative research with a descriptive approach and uses Charles Sanders Pierse's semiotic analysis theory, known as the triadic concept, to find out the representanment, interpretant, and objects in the signs on the video account of the tiktok @aabelkarimi. The results of the study show that there are da'wah messages contained in the @aabelkarimy tiktok account. The da'wah message includes aspects of aqidah, shari'ah, morals. In the aspect of aqidah there are da'wah messages in the form of; faith in God includes the belief that humans are weak creatures created by God, lacking and limited. In the aspect of shari'ah there is a message about the obligation of preaching to the authorities. Whereas in the moral aspect there is a message in the form of a recommendation to have a qanaah attitude in life. In relation to Charles Sanders Pierse's semiotic analysis, on the video of the tiktok account @aabkarimi there is a sign meaning based on representament, object and interpretant Keywords: Semiotic Analysis, Da'wah Messages, Tiktok